Pelatihan Pembuatan Kerajinan Tangan Menggunakan Kain Flanel di Wilayah RT3/RW 3 Kelurahan Tanjung Uma - Ryan Swardana; Elvi Mellina; Jensen Kho; Leonardo Aprilson; Christy Christy; Nelson Nelson; Yulita Karolina Bunga; Frans Hadinata; Pendi Ang; Meikel Meikel (National Conference for Community Service Project (NaCosPro), 2019)
Society Empowerment Program or known as SEPORA is a social activities program where students have to do community service activities in a certain area. The activities that can be carried out in this program is counseling, education, training and many more On this occasion the authors doing community service activities in RT 03 RW 03 Tanjung Uma Village. Based on the results of our visit there were many things that became the problem of the village. one of the problems is the children are addicted to playing gadgets all day long. Playing gadgets actually have positive and negative effects on the child's growth, but if you play the gadget continuously and all day long it will certainly have negative impacts on the children. The purpose of these activities is to encourage the children to fill their daily activity with positive activities by learning handicrafts. By doing something creative, you allow children to express their feelings by providing opportunities for trying out new ideas, new ways of thinking and problem-solving. The result that we achieve from doing these activities together is very satisfying as it trains our creativity and teamwork.